A real-word study: is normothermic intraoperative intraperitoneal chemotherapy impactful as we expect? - Jin, Mengyao; Cao, Wei; Chen, Junjie; Xiong, Maoming; Cao, Guodong; Chen, Bo (Frontiers in Oncology, 2023)
Background: Patients with gastric cancer have a poor prognosis. Currently, intraperitoneal chemotherapy has been considered a therapeutic option to improve prognosis due to its appealing theoretical rationales. But there is no consensus on the choice of chemotherapeutic agents used in intraperitoneal chemotherapy for gastric cancer. The real-world efficacy of applying intraoperative chemotherapy in gastric cancer still remains undefined. Methods: Patients with gastric cancer who underwent radical gastrectomy at the Gastrointestinal Department of The First Affiliated Hospital of Anhui Medical University between 2012 and 2019 were enrolled in this study. Patients were divided into two groups based on whether they received intraperitoneal chemotherapy. The t-test (mean of two samples) was conducted to compare the difference in measurement data between the two groups, and the chi-square test was used to compare the difference in count data. Kaplan-Meier method with log-rank test was performed to analyze the overall survival of patients. Kaplan-Meier method with log-rank test was also performed in various subgroups to respectively compare the survival of patients. Multivariate Cox analysis was performed to analyze the prognosis factors of these patients. Results: A total of 1253 patients were included in the final analysis, in which 861 patients received intraperitoneal chemotherapy and 352 not received intraperitoneal chemotherapy. The clinicopathological features of the participants in the two groups were comparable. There was no significant difference between the two groups in overall survival (P > 0.05). Consistently, no significant difference was found between the two groups in each subgroup (P > 0.05). The multivariate Cox analysis demonstrated that only age, BMI, pathological type, TNM stage, and differentiation grade were independent risk factors of survival.